QBD-OPTIMISED AND VALIDATED RP-HPLC METHOD DEVELOPMENT USING BOX-BEHNKEN DESIGN FOR QUANTITATIVE EVALUATION OF DASATINIB IN LIPID NANOPARTICLES - KEERIKKADU, MAHESHA; DEVANAND BANGERA, PRAGATHI; SHETTY, AKSHAY; TIPPAVAJHALA, VAMSHI KRISHNA; RATHNANAND, MAHALAXMI (International Journal of Applied Pharmaceutics, 2026)
Objective: A robust and reliable analytical method for the quantification of dasatinib (DSB) is required for the design of such lipid nanoparticle (LNP) systems, as excipients may interfere and the drug may be unstable during analysis. Methods: A Quality by Design (QbD) approach was employed in the development and optimization of a reversed-phase high performance liquid chromatography (RP-HPLC) method using a box-behnken design (BBD) to explore the relationships between the important variables in the chromatographic process. The optimized method was validated as per ICH guidelines, and it was found to be linear in the range of 50 to 5000 ng/mL with a good concentration-response relationship. Results: The method demonstrated excellent sensitivity, with limits of detection and limits of quantitation of 3.16 ng/mL and 9.56 ng/mL, respectively. Precision testing showed the method had good repeatability and percentage relative standard deviation (%RSD) within acceptable ranges. The method also demonstrated specificity via photodiode array detector (PDA) peak purity analysis, which yielded a purity index of 0.999, indicating no interference from excipients or degradation products. Forced degradation testing Experiments provided evidence that DSB was exhibited 13.91% degradation under acidic conditions (0.1 N HCl, room temperature (RT)) and 13.42% degradation under alkaline conditions (0.1 N NaOH, RT) and that the separation of intact Drug from Degradation Products supported the method's ability as a stability-indicating method on the dasatinib lipid nanoparticles (DSB-LNPs), with a 97.43% of percentage encapsulation efficiency (%EE) , 3.98% of percentage drug loading (%DL), supporting its use in routine analysis. Conclusion: The validated QbD approach-based RP-HPLC method is robust, sensitive, and stability-indicating; therefore, it is the best choice for routine analysis of DSB in Bulk and LNPs.